Goal modification, learning styles and achievement in mathematics - Joaquin, Ma. Nympha Beltran (Education quarterly.)
This study investigated whether mastery and competitive goals could be developed among students, while controlling for the possible effects of student learning styles. A pretest-posttest control group designed was used in this 10-week experiment that employed three intact school mathematics classes. Results showed that mastery and competitive goals could be separately modified among students. However learning styles did not moderate the effects of these goal modifications. The study further investigated which of these three goals - mastery, competitive, and avoidance - predicts achievement in mathematics.